PENGARUH INDEPENDENSI, KOMPETENSI, OBYEKTIVITAS, SKEPTISME PROFESSIONAL TERHADAP KUALITAS AUDIT DENGAN KECERDASAN SPIRITUAL SEBAGAI VARIABEL MODERATING - Wahyu Wahyudin; Fitriana; Didin Saefudin (Universitas Widyatama, 2021)
Professional skepticism on audit quality with spiritual intelligence as a moderating variable (empirical study at the inspectorate office of regency / city government in West Java province)